Investigate Temperature Preheating on the Chill Plate to Identify Surface Characteristic on the Ductile Iron by Sand Casting (International Journal of Engineering Materials and Manufacture, 2021)
The chilled casting method is widely used in the metal casting industry to accelerate the mold's cooling rate. This method is very suitable for surface hardening by depositing the elements contained in the chill material onto the surface of the object being cast. One of the factors that influence surface hardness characteristics is the diffusion temperature. This study aims to determine the microhardness, surface layer thickness, and the element contained on the surface. The main material produced into Y-Block is ductile cast iron, the chill material is SS 304 plate with a thickness of 0.2mm. However, before the liquid material is poured into a mold, the chill plate is inserted into the surface of the pattern in the mold, then the plate was preheated. The result showed that the highest preheating temperature has produced microstructure around the surface area namely eutectic carbide of (FeCr)7C3, and (FeCr)3C. SEM-EDX analysis shows that 7.13%Cr is contained on the coating layer at a thickness of 0.020 mm and an average hardness of 700-900 HV.